The grounding of modern feminism - Cott, Nancy F. (Yale University Press, 1987)
Nancy F. Cott offers a new interpretation of feminism in the United States during the early decades of the century -- a period traditionally viewed as one in which women won the right to vote and then lost interest in feminist issues. Cott contends that the decades between 1910 and 1930 revealed a crisis of transition in which the nineteenth-century "woman movement" was left behind and modern feminism was inaugurated. Cott argues that in contrast to the nineteenth-century "cause of woman" or claim for "woman's rights"--In which the singular noun symbolized the unity of the female sex-- feminists of the early twentieth century wished to refute the premise of a singular "woman": they recognized increasing heterogeneity and diverse loyalties among women, and championed individual variability. This history -- the story of women who first claimed the name of feminists -- builds a necessary bridge between the presuffrage era and today. -- From publisher's description